Allan Hancock Pacific Expeditions. - Dawson, Elmer Yale (The University of Southern California Press, 1941)
Contents : The University of Southern California Publications Allan Hancock Pacific Expeditions Vol. 3 nos. 7, 8 Contents: (1) Field observation s on the algae of the Gulf of California (2) A review of the Genus Rhodymenia with descriptions of new species